THE HISTORY OF DEVELOPMENT OF THE SURGICAL SERVICE OF SKLIFOSOVSKY RESEARCH INSTITUTE FOR EMERGENCY MEDICINE IN THE FIRST HALF OF THE TWENTIETH CENTURY - M. Sh. Khubutia; M. M. Abakumov; S. A. Kabanova; P. M. Bogopolsky (Неотложная медицинская помощь, 2016)
The history of the formation and improvement of the surgical service of the Sklifosofsky Research Institute for Emergency Medicine since its founding in 1923 until 1951 is set out. For this goal the published works of employees of the Institute and archival documents are brought. It is shown that the structure of the surgical service during the first half of the twentieth century has steadily expanded, rebuilt and improved depending on changes in the clinical and scientific problems.